Researchers on ice? How the COVID-19 pandemic has impacted Antarctic researchers - Liggett, Daniela; Herbet, Daniela; Badhe, Renuka; Charnley, Gina; Hudson, K.P.C.; Kelman, Ilan; Won Sang, Lee; Lorenzo, Cristian A.; Marques Quinteiro, Pedro; Nash, Meredith; Pickett, Jennifer; Yermakova, Yelena (Antarctic Science)
The COVID-19 pandemic and pandemic-related measures have impacted the lives and work-related activities of Antarctic researchers. To explore these impacts, we designed, piloted and disseminated an online survey in English, Russian, Spanish and Chinese in late 2020 and early 2021. The survey explored how the pandemic affected the productivity of Antarctic researchers, their career prospects and their mental wellbeing. Findings exposed patterns of inequities. For instance, of the 406 unique responses to the survey, women appeared to have been affected more adversely than men, especially in relation to mental health, and early-career researchers were disadvantaged more than their mid- or late-career colleagues. Overall, a third of the research participants reported at least one major negative impact from the pandemic on their mental health. Approximately half of the participants also mentioned that the COVID-19 pandemic had some positive effects, especially in terms of the advantages that working from home brought and opportunities to attend events, network or benefit from training workshops online. We conclude with a series of recommendations for science administrators and policymakers to mitigate the most serious adverse impacts of the pandemic on Antarctic research communities, with implications for other contexts where scientific activities are conducted under extreme circumstances. Fil: Liggett, Daniela. University of Canterbury; Nueva Zelanda Fil: Herbet, Daniela. University of Canterbury; Nueva Zelanda Fil: Badhe, Renuka. European Polar Board; Países Bajos Fil: Charnley, Gina. Imperial College London; Reino Unido Fil: Hudson, K.P.C. University of Vermont; Estados Unidos Fil: Kelman, Ilan. University College London; Estados Unidos. University of Agder; Dinamarca Fil: Won Sang, Lee. Korea Polar Research Institute; Corea del Sur Fil: Lorenzo, Cristian A. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de ...